Predictive factors for initial treatment response after circumferential radiofrequency ablation for Barrett’s esophagus with early neoplasia: a prospective multicenter study - van Vilsteren, F. G. I.; Alvarez Herrero, L.; Pouw, R. E.; Schrijnders, D.; Sondermeijer, C. M. T.; Bisschops, R.; Esteban, J. M.; Meining, A.; Neuhaus, H.; Parra-Blanco, A.; Pech, O.; Ragunath, K.; Rembacken, B.; Schenk, B. E.; Visser, M.; Kate, F. J. W. ten; Meijer, S. L.; Reitsma, J. B.; Weusten, B. L. A. M.; Schoon, E. J.; Bergman, J. J. G. H. M. (Endoscopy, 2013)
Background and study aims: Radiofrequency ablation (RFA) is safe and effective for the eradication of neoplastic Barrett’s esophagus; however, occasionally there is minimal regression after initial circumferential balloon-based RFA (c-RFA). This study aimed to identify predictive factors for a poor response 3 months after c-RFA, and to relate the percentage regression at 3 months to the final treatment outcome.Methods: We included consecutive patients from 14 centers who underwent c-RFA for high grade dysplasia at worst. Patient and treatment characteristics were registered prospectively. “Poor initial response” was defined as < 50 % regression of the Barrett’s esophagus 3 months after c-RFA, graded by two expert endoscopists using endoscopic images. Predictors of initial response were identified through logistic regression analysis. Results: There were 278 patients included (median Barrett’s segment C4M6). In poor initial responders (n = 36; 13 %), complete response for neoplasia (CR-neoplasia) was ultimately achieved in 86 % (vs. 98 % in good responders; P < 0.01) and complete response for intestinal metaplasia (CR-IM) in 66 % (vs. 95 %; P  < 0.01). Poor responders required 13 months treatment (vs. 7 months; P < 0.01) for a median of four RFA sessions (vs. three; P < 0.01). We identified four independent baseline predictors of poor response: active reflux esophagitis (odds ratio [OR] 37.4; 95 % confidence interval [CI] 3.2 – 433.2); endoscopic resection scar regeneration with Barrett’s epithelium (OR 4.7; 95 %CI 1.1 – 20.0); esophageal narrowing pre-RFA (OR 3.9; 95 %CI 1.0 – 15.1); and years of neoplasia pre-RFA (OR 1.2; 95 %CI 1.0 – 1.4). Conclusions: Patients with a poor initial response to c-RFA have a lower ultimate success rate for CR-neoplasia/CR-IM, require more treatment sessions, and a longer treatment period. A poor initial response to c-RFA occurs more frequently in patients who regenerate their endoscopic resection scar with Barrett’s epithelium, and those with ongoing reflux esophagitis, neoplasia in Barrett’s esophagus for a longer time, or a narrow esophagus.